Biographieforschung: Analyse der Berufslaufbahn von Schauspielern - Haack, Imke (Forum Komparative Kasuistik, 2009)
Careers of actors are to a large degree influenced by significant ups and downs. That is why is the profession of the actor is particularly well to study for career decision moments, crises and turning points in a biographical way. Special attention was directed on the auto-genetic aspects of the lives of actors. The main interest focused on topics such as success and failure, objectives and decisions, work ethic, relationship with colleagues, directors and audiences, job search and unemployment, job satisfaction and high and low points of his career. 16 theater and film actors were divided according to their job satisfaction and then qualitative, semi-structured interviews were conducted with them. The analysis was performed by using methods of comparative case report (Jüttemann, 1990) and the circulatory deconstructing (Jaeggi & Faas, 1991). The results are illustrated by themes like "Reasons to be an actor", "A production can be hell" and "Without a safety net" sorted and with numerous examples and interview quotations presented alive.